Results of a multicenter 4D computed tomography quality assurance audit: Evaluating image accuracy and consistency - Burghelea, Manuela; Bakkali Tahiri, Jinane; Dhont, Jennifer; Kyndt, Martin; Gulyban, Akos; Szkitsak, Juliane; Bogaert, Evelien; van Gestel, Dirk; Reynaert, Nick (Physics and Imaging in Radiation Oncology, 2023)
Background and purpose: 4D Computed Tomography (4DCT) technology captures the location and movement of tumors and nearby organs at risk over time. In this study, a multi-institutional multi-vendor 4DCT audit was initiated to assess the accuracy of current imaging protocols. Materials and methods: Twelve centers, including thirteen scanners performed a 4DCT acquisition of a dynamic thorax phantom using the institution's own protocol with the in-house breathing monitoring system. Five regular and three irregular breathing patterns were used. Image acquisition and reconstruction were followed by automated image analysis with our in-house developed 4DCT QA program (QAMotion). CT number accuracy, volume deviation, amplitude deviation, and spatial integrity were assessed per pattern using both the segmented volumes and line profiles. Results: Regular breathing curves showed relatively accurate results across all institutions, with mean volume and CT number deviations and median amplitude deviation below 2%, 5 HU and 2 mm, respectively. Results obtained for irregular patterns showed more variation across the institutions. Volume and CT number deviations co-occurred with a blurring of the sphere, interpolation, or double-structure artifacts that were confirmed through the line profiles. For some of the irregular patterns, amplitude deviations up to 6 mm were observed. Maximum Intensity Projection (MaxIP) correctly captured the applied motion amplitude with deviations across all institutions within 2 mm except for double amplitude pattern. Conclusions: All centers invited to participate in the audit responded positively, highlighting the need for a comprehensive yet easy-to-execute 4DCT quality assurance program. The largest variances between the results from one institution to another confirmed that a standardized 4DCT audit is warranted.
CRIS-Team Scopus Importer:2023-09-15